Padrões de coordenação interpessoal no futebol: análise das relações numéricas relativas em sequências ofensivas finalizadas em gol - Santos, Rodrigo de Miranda Monteiro (Universidade Federal de Viçosa, 2015)
The aim of this dissertation was to verify how the analysis of interpersonal coordination in soccer might contribute to the identification of emergent patterns of play in goal-scoring possessions in open play. The document comprises three scientific papers. The first paper highlights that the study of interpersonal coordination in soccer has recently become an emergent research topic. Several studies that have investigated the different levels of interactions (dyads, sub-groups and teams), which comprise soccer competition, aimed to comprehend how coordination between players and teams arises as well as to identify the emergent patterns from such interactions. Therefore, this leading article aimed: (i) to provide a brief description of the background regarding the main concepts within the topic of coordination; (ii) to highlight the most relevant studies and findings regarding the study of interpersonal coordination in soccer and (iii) to discuss the implications of these studies and findings for representative task design. It is reasonable to suggest that the design of representative tasks in training and testing should rely upon the performances and behaviours observed in actual match contexts. The purpose of the second paper is to present a novel computational tool to analyze inter-team coordination patterns in soccer from video footage. The paper describes the design of low-cost and straightforward manual tracking procedures in comparison with some expensive and highly complex automatic tracking systems currently available. High reliability values suggest that this tool can be employed in a great variety of contexts in soccer and other team sports. The third paper aimed to examine the emergent inter-team coordination tendencies from goal-scoring possessions in open play of the 2014 FIFA ® World Cup winner team, through the analysis of teams' numerical relations within the effective play-space (EP-S). We assume that Germany generate more numerical uncertainty in sub-areas of play closer to opponents' goal in goal- scoring possessions. We analysed 6457 frames from 11 video sequences of goal- scoring possessions in open play during that tournament. Teams' numerical relations within sub-areas of play were examined in each offensive sequence through Shannon's entropy, H. The uncertainty of numerical relationships between the teams across sub-areas was also calculated. Entropy measures indicated that the uncertainty of teams' numerical relations was higher within the German Central Offensive (opponents' Central Defensive) sub-area (1.86 bits) in comparison with the remaining sub-areas of play. These results confirm our initial hypothesis, displaying that, in goal-scoring possessions, the German team generates more numerical uncertainty in critical offensive sub-areas of play. Future research should verify whether such pattern is a predominant feature in successful teams.

O objetivo deste trabalho foi verificar como a análise da coordenação interpessoal no futebol pode contribuir para a identificação de padrões de jogo emergentes a partir de sequências ofensivas finalizadas em gol. O documento está estruturado em três artigos científicos. O primeiro artigo destaca que o estudo da coordenação interpessoal no futebol vem se tornando um tópico de pesquisa emergente. Com o propósito de compreender como surge a coordenação entre jogadores e equipes, bem como identificar os padrões emergentes destas interações, diversos estudos têm investigado os diferentes níveis de interação (díades, subgrupos e equipes) que descrevem o jogo de futebol. Desta forma, os objetivos deste artigo foram: (i) fornecer uma breve descrição do background relativo aos conceitos que envolvem o tópico de coordenação; (ii) destacar os estudos e achados mais relevantes relativamente à investigação da coordenação interpessoal no futebol e (iii) discutir as implicações destes estudos e resultados o desenvolvimento de tarefas representativas em treino e pesquisa. Parece razoável sugerir que o desenvolvimento de tarefas representativas deve basear-se nos comportamentos e desempenhos observados em contextos reais de jogo. O segundo artigo objetivou a apresentação de uma nova ferramenta informática para análise de padrões de coordenação entre equipes de futebol a partir de imagens de vídeo. O instrumento inclui procedimentos objetivos e de baixo custo, em comparação aos caros e complexos sistemas de rastreamento automático disponíveis atualmente. Altos valores de fiabilidade indicam que esta ferramenta pode ser empregada em uma grande variedade de contextos no futebol e também em outros esportes coletivos. O terceiro artigo teve por objetivo identificar tendências de coordenação entre equipes a partir das sequências ofensivas finalizadas em gol da equipe campeã da Copa do Mundo FIFA ® 2014. Foram analisados 6457 quadros de vídeo (unidade de análise) de 11 cenas de vídeo de sequências ofensivas finalizadas em gol. A incerteza das relações numéricas das equipes dentro das subáreas de jogo foi analisada em cada sequência ofensiva através da entropia de Shannon. Os valores de entropia indicaram que a incerteza das relações numéricas das equipes foi maior na subárea Ofensiva Central da seleção alemã (subárea Defensiva Central adversária; 1,86 bits) em comparação ao restante das subáreas de jogo. Estes resultados sugerem que em sequências ofensivas finalizadas em gol, as relações numéricas relativas foram mais imprevisíveis na subárea do Espaço de Jogo Efetivo (EJE) mais próxima à baliza adversária. Futuros estudos devem verificar se este padrão é uma característica predominante em equipes bem sucedidas.
Interpersonal coordination in soccer: analysis of patterns of relative numerical relations in goal-scoring possessions
Keywords: Futebol; Entropia; Futebol - Treinamento técnico; Educação Física